Constitutional Rights, Collective Bargaining and the Supreme Court of Canada: Retreat and Reversal in the Fraser Case - Fudge, Judy (Industrial Law Journal, 2012)
The scope of labour rights that are protected by constitutional protections of freedom of association is highly contested and, increasingly, is being litigated before courts. In Canada, the Supreme Court began in 2001 to chip away at jurisprudence that provided a narrow interpretation of freedom of association, and, in 2007, it over-ruled precedent to hold that freedom of association includes collective bargaining. However, this incremental expansion of the freedom of association to include core labour rights came to a halt in the Supreme Court's April 2011 decision Attorney General of Ontario v Fraser. Although a majority of the Court agreed that freedom of association includes collective bargaining, Fraser is remarkable for the extent of disagreement amongst members of the Court over the scope of collective bargaining and how this disagreement has influenced the tone and cogency of the Court's reasoning. This article begins by providing a history of the successive rounds of litigation leading to the Supreme Court's decision in Fraser. This legal context is important because it is barely visible in the majority and concurring judgments, which read as if collective bargaining rights for agricultural workers were a subsidiary concern, and not the issue in dispute. The article then examines the four judgments that make up the Supreme Court of Canada's decision in Fraser, focusing exclusively on the freedom of association arguments. The implications of the Fraser decision for the immediate future of constitutional litigation and labour rights in Canada are discussed in the final section.